2022
DOI: 10.1002/ael2.20066
|View full text |Cite
|
Sign up to set email alerts
|

Response of black cumin to vermicompost and nitrogen fertilizer

Abstract: An experiment was conducted to evaluate the response of black cumin (Nigella sativa L.) to vermicompost and nitrogen (N) fertilizer rates. Four rates of vermicompost and four rates of N were laid out in a randomized complete block design with three replications. The results showed that the interaction effects of nitrogen fertilizer and vermicompost rates significantly influenced black cumin growth, yield, and yield component parameters. The maximum seed yield (1,090 kg ha–1) was obtained from the combined appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Increased grain yield with the consumption of 80 kg N/ha has been reported in black seed (Tulukcu, 2016). Increasing grain yield using low nitrogen levels in the study on soybean (Epie et al, 2022), black seed (Wako et al, 2022), barley (Armand et al, 2016), and pumpkin (Aghaee and Ehsanzadeh, 2011) has been reported. The increase in black seed yield with nitrogen consumption can be due to the effective role of nitrogen in the structure of chlorophyll, photosynthetic rate, and plant growth (Anas et al, 2020).…”
Section: Seed Yieldmentioning
confidence: 97%
“…Increased grain yield with the consumption of 80 kg N/ha has been reported in black seed (Tulukcu, 2016). Increasing grain yield using low nitrogen levels in the study on soybean (Epie et al, 2022), black seed (Wako et al, 2022), barley (Armand et al, 2016), and pumpkin (Aghaee and Ehsanzadeh, 2011) has been reported. The increase in black seed yield with nitrogen consumption can be due to the effective role of nitrogen in the structure of chlorophyll, photosynthetic rate, and plant growth (Anas et al, 2020).…”
Section: Seed Yieldmentioning
confidence: 97%